Myocardial infarction impaired wall mechanics and hemodynamics in peripheral arteries - Xue, Qiang; Shi, Hongyu; Li, Li; Jin, Qing; Wang, Xuan; Huo, Yunlong (Frontiers in Physiology, 2023)
Myocardial infarction (MI) impaired both cardiac functions and peripheral arteries. The changes in normal and shear stresses in the peripheral artery wall are of importance for understanding the progression of MI-induced heart failure (HF). The aim of the study is to investigate the corresponding changes of normal and shear stresses. The coronary artery ligation was used to induce the MI in Wistar rats. The analysis of wall mechanics and hemodynamics was performed based on in vivo and in vitro measurements. Myocardial infarction increased wall stiffness in elastic carotid and muscular femoral arteries significantly albeit different changes occurred between the two vessels from 3 to 6 weeks postoperatively. Moreover, the hemodynamic analysis showed the gradually deteriorated wall shear stress, oscillatory shear index and relative residence time in the two arteries. This study probably shed light on understanding the interaction between abnormal systemic circulation and peripheral mechanics and hemodynamics during the development of MI-induced HF.